Time course of attentional bias to cigarette-related cues in male smokers with different working memory updating abilities - Zhang, Yang; Qiao, Yaya (Current psychology (New Brunswick, N.J.), 2025)
Although smokers' attentional bias toward cigarette-related cues has been extensively studied, it remains unclear whether working memory updating ability within the top-down cognitive control system can modulate this bottom-up automatic attentional bias mechanism. Investigating their interactive relationship would not only deepen our understanding of the cognitive mechanisms underlying nicotine dependence, but also provide a theoretical foundation for developing cognitive training-based smoking intervention strategies. This study aims to examine the behavioral differences in attentional orienting and disengagement among smokers with high/low working memory updating ability when exposed to cigarette-related cue stimuli with varying presentation durations. One hundred and twenty male smokers completed a 3-back task to measure their working memory updating ability. All participants were ranked from fast to slow according to their reaction times in the task: the fastest 27% of the subjects were assigned to the high working memory updating group, and the slowest 27% to the low working memory updating group. Thereafter, both groups completed a dot-probe task to measure their attentional orienting and attentional disengagement difficulties associated with cigarette-related cues at different stimulus presentation times (200 ms and 500 ms). When picture stimuli were presented for 200 ms and 500 ms, smokers with low working memory updating ability had significantly greater difficulty in disengaging from cigarette-related cues, while smokers with high working memory updating ability had no significant difficulty in disengaging. This study reveals the pivotal role of advanced cognitive functions in regulating attentional bias among smokers, providing a significant theoretical foundation and practical direction for the development of cognitive training-based intervention strategies for attentional bias.